DEVELOPMENT OF SREMSKI KARLOVCI WINE TOURISM AND INTEGRATION IN THE REGIONAL TOURISM OFFER - Škrbić, Iva; Jegdić, Vaso; Milošević, Srdjan; Tomka, Dragica (Economics of Agriculture, 2015)
Integration and globalisation processes are unavoidable in all fields of business economy, including tourism. Potential success of wine tourism in Sremski Karlovci should be based on diversification of products that entails an influx of tourism and winemaking into other fields of economy. During the development of wine tourism offer, it would be advisable to consult the experiences of the developed wine region and to use their models, which is done in this paper, via benchmark analysis of offers of Sremski Karlovci wineries with those of the Ontario region (Canada) and the place of Villány (Hungary). The goal of this paper is to establish the possible directions of development of the integral product of wine tourism of Sremski Karlovci as a prerequisite for integration into the regional tourism offer. The research indicates that wine tourism offer of Sremski Karlovci is underdeveloped. A large number of product diversification fields are not recognised. The future development of Sremski Karlovci wineries should be based on conquering of those very fields. Such a tourism product could more easily be integrated into the regional wine tourism offer.